The Effect of the District Court Judge's Verdict in the Sambo CS Case on the Level of Public Trust in the Criminal Justice System in Indonesia - Endro Tri Susdarwono; Alma Wiranta (Recht Studiosum Law Review, 2023)
This study aims to provide a description regarding the influence of the District Court judge's verdict in the Sambo cs case on the level of public trust in the criminal justice system in Indonesia. The approach in this study uses a type of quantitative research. The sample of respondents consisted of 200 respondents located in Brebes Regency, Tegal Regency, Tegal City and Pemalang Regency. The sampling technique used non-random sampling with purposive sampling. While the instrument used in this research is a questionnaire. The data analysis technique uses the independence hypothesis test through the Khai-Square distribution. This study concludes that based on the calculation results, the khai-squared value is 62.586. Thus, the null hypothesis is rejected and the alternative hypothesis is accepted. In fact, the District Court judge's verdict in the Sambo cs case did influence the level of public trust in the criminal justice system in Indonesia.